The Bottom billion : why the poorest countries are failing and what can be done about it - Collier, Paul (New York Oxford University, 2009)
​Global poverty is falling rapidly but in fifty or so failing states the world's poorest peopole the "bottom people" - face a tragedy that is growing inexorably worse. Why do these states defy all attempts to help them? Why dies current aid seem unable to make a difference? In his award-winning bestseller, Paul Collier inpoints the issues of corruption, political instability, and resource management that lie at the roof of the problem, and offers hard-nosed solutions and real hope for a way of solving one of the greatest crises facing the whole world
​Preface --  Part 1 : What's the issue 1. Falling behind and falling apart : the bottom billion --  Part 2: the Traps 2. The conflict trap -- 3. The natural resource trap -- 4. Landlocked with bad neighbors -- 5. Bad governance in a small country --  part 3 : An Interlude: globalization to the rescue 6. On missing the boat : the marginalization of the bottom billion in the world economy --  Part 4:  the Instruments  7. Aid to the rescue? -- 8. Military intervention -- 9. Laws and charters -- 10.Trade policy for reversing marginalization -- Part 5: The Struggle for the bottom billion 11. An agenda for action
​Includes bibliographical references and index